2013
DOI: 10.1093/nar/gkt812
|View full text |Cite
|
Sign up to set email alerts
|

Defective chromatin recruitment and retention of NHEJ core components in human tumor cells expressing a Cyclin E fragment

Abstract: Exposure to genotoxic agents, such as ionizing radiation (IR), produces double-strand breaks, repaired predominantly in mammalian cells by non-homologous end-joining (NHEJ). Ku70 was identified as an interacting partner of a proteolytic Cyclin E (CycE) fragment, p18CycE. p18CycE endogenous generation during IR-induced apoptosis in leukemic cells and its stable expression in epithelial tumor cells sensitized to IR. γH2AX IR-induced foci (IRIFs) and comet assays indicated ineffective NHEJ DNA repair in p18CycE-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…These results indicate that by interacting with DNA-PKcs TMPRSS2-ERG does indeed inhibit DNA-PKcs Thr2609 and Ser2056 auto-phosphorylation required for its function. Finally, we and others have shown that Ser1778 is a 53BP1 C-terminal phosphorylation target of DNA-PKcs (37, 38) that contributes significantly to DNA repair after IR (39). Ser1778 53BP1 foci were also absent in PC3 cells expressing TMPRSS2-ERG (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…These results indicate that by interacting with DNA-PKcs TMPRSS2-ERG does indeed inhibit DNA-PKcs Thr2609 and Ser2056 auto-phosphorylation required for its function. Finally, we and others have shown that Ser1778 is a 53BP1 C-terminal phosphorylation target of DNA-PKcs (37, 38) that contributes significantly to DNA repair after IR (39). Ser1778 53BP1 foci were also absent in PC3 cells expressing TMPRSS2-ERG (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The key regulators in response to DNA damage are ATM and ATR kinases, which activated Chk1 and Chk2 [40]. The phosphorylation of ATM/ATR and Chk1/Chk2 was increased by Cuc B, which were dramatically inhibited by ATM inhibitor, KU55933 [41], and ATM/ATR inhibitor caffeine [42]. Thus, Cuc B-induced DNA damage response was mediated by ATM/ATR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated whether specific DNA-PKcs inhibitor NU7441 can induce detectable changes in DNA-PKcs phosphorylation status. It has previously been shown that NU7741 inhibits formation of S2056 foci (19), while the inhibitor treatment does not affect formation of T2609 foci or significantly affect ATM or ATR activity (20). AG07217 and HCT116 cells were treated with 5 lM NU7441 for 1 h, irradiated, fixated and stained, and cells in asynchronous population were then analyzed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to discriminate between wild-type and ligase IV hypomorphic cells can be useful in the characterization of SCID patients and in the selection of appropriate cancer therapies. We and others have previously shown that treatment with NU7441 does not prevent formation of pDNA-PKcs foci (19,22,23). Therefore, in this study we used NU7441 to delay the phosphorylation of DNA-PKcs, which was successfully measured using flow cytometry.…”
Section: Discussionmentioning
confidence: 99%